The Role of Learning Communities as A Means of Teacher Professionality Development at SDN 1 Srobyong - Agustin, Indah Sari; Zumrotun, Erna (Jurnal Ilmiah Pendidikan Dasar, 2024)
Teacher professionalism is very important to improve student learning outcomes. For this reason, learning communities exist as a means of developing teacher professionalism. This research aims to analyze the role of learning communities in the professional development of elementary school teachers, identify the obstacles and challenges faced, and find solutions to overcome obstacles and challenges when participating in learning communities. This research method is qualitative case study research. Data collection techniques include in-depth interviews, focus group discussions, and participatory observation. The data collection technique used purposive sampling, the researcher chose subjects, namely 3 teachers including the community leader, class teacher, and PAI subject teacher. The data analysis technique uses Milles and Huberman qualitative analysis. Learning communities in elementary schools have an important role in developing teacher professionalism. The novelty of this research is the use of technology, especially the Merdeka Mengajar Platform (PMM) to facilitate collaboration and share teacher knowledge in learning communities. As well as using a holistic approach to pedagogical competence and developing soft skills such as leadership and collaboration. The obstacles and challenges found included limited time, school support, and motivation. Solutions to overcome this include institutional support, strategies to increase teacher participation, technology-based implementation approaches, and curriculum development with the community. Therefore, this article makes a significant contribution to efforts to increase the capacity of elementary school teachers through more active participation in learning communities, so that it can become a reference for increasing the effectiveness of the existing education system in Indonesia.